Promoting Gender Equality in EU Development Aid: From Transformative Policy to Transformative Practice? - Debusscher, Petra (Kvinder, Køn & Forskning, 2011)
Promoting gender equality in EU development aidThe European Commission combines specific funds for women’s empowerment with gender mainstreaming in its twin-track approach to gender equality in development aid policies. The strategy is successful in terms of budgets and formal appearance but it is implemented in a limited, interest-guided and expertbureaucratic manner. Furthermore by privileging EU interests the strategy fails to address the needs of the poorest developing countries and it ignores civil society concerns. In practice, the twin-track strategy severely limits the transformative potential of gender equality policies.